Cancer Stem Cell Markers Are Associated With Distant Hematogenous Liver Metastases But Not With Peritoneal Carcinomatosis in Colorectal Cancer. (14th September 2015) - Neumann, Jens; Löhrs, Lisa; Albertsmeier, Markus; Reu, Simone; Guba, Markus; Werner, Jens; Kirchner, Thomas; Angele, Martin
Abstract : Although peritoneal carcinomatosis (PC) displays advanced stage in colorectal cancer (CRC), most patients present without distant metastases. To analyze the expression of cancer stem cell markers immunohistochemistry for CD133, CD44 and β-catenin was applied to CRC with exclusive PC, exclusive hepatic metastasis and CRC with combined spread. Expression of cancer stem cell markers correlated with hematogeneous metastases to the liver and was absent in patients with exclusive PC. Thus, expression of cancer stem cell markers correlates with different patterns of metastatic spread in CRC. These data indicate that CRC with exclusive PC lack stem cell features needed for distant dissemination.